Discrimination and cognitive failures in Singapore and the US: An investigation of between- and within-persons associations through multilevel modelling - NADYANNA BINTE MOHAMED MAJEED, (Institutional Knowledge at Singapore Management University, 2023)
Experiencing everyday discrimination can have a significant negative impact on an individual’s wellbeing. While much attention has been paid to the physical and mental health consequences of discrimination, less is known about how discrimination can affect cognitive health, and most existing work has been conducted in laboratory settings where participants recall discrimination retrospectively. Given the artificial environment and susceptibility to recall bias in such procedures, the current study utilised two daily diary studies, consisting of young adults in Singapore (Study 1; N = 484) and midlife adults from the US (Study 2; N = 3577), to examine the association between discrimination and cognitive failures in daily life. Multilevel modelling revealed consistent evidence that experiencing discrimination was associated with poorer cognitive health at both the within- and between-person levels. These associations between discrimination and cognitive health remained robust even after controlling for demographic covariates previously found to affect cognitive health, as well as daily stressor exposure. These findings suggest that the experiences of everyday discrimination may lead to poorer daily cognitive functioning regardless of whether discrimination was experienced in a daily context or across the lifespan, and indicate importance of raising awareness on the harmful cognitive consequences of discrimination.